Development and validation of the Individual Empowerment Scale in the context of chronic disease - Luz, Elisabete Lamy da (2020)
Background: The assessment of empowerment can contribute to obtaining gains in health. Objectives: To develop and validate a scale for assessing the individual empowerment of chronically ill people. Methodology: The instrument was developed and applied to a convenience sample of 271 chronically ill people, between 18 and 65 years old, residing in Lisbon. The validation of the reliability of the instrument was carried out to assess the metric properties of the scale. Results: A 25-item scale was developed with 7 dimensions: Self-perception, Participation in health-related decisions, Mastery, Determination, Identity, Autonomy and power, and Relationship with health professionals. The factor analysis (principal components analysis with Varimax rotation) revealed that the 25 items were organized into seven factors with a total variance explained of 65.28% and a total Cronbach’s alpha of 0.803. Conclusion: The creation of a valid and reliable measure of the empowerment of chronically ill people may assist health professionals in exploring the impact of this outcome on treatment regimen self-management